2006
DOI: 10.1111/j.1439-0418.2006.01037.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irradiation on female painted apple moth Teia anartoides (Lep., Lymantriidae) sterility and attractiveness to males

Abstract: Live female painted apple moths are being used to monitor the distribution of this invasive species in Auckland as part of a major eradication effort, and the goal of this project was to develop a method to minimize the risk of unwanted live insect propagation from the trapping programme as a result of vandalism or Ôeco-terrorismÕ. Female pupae were irradiated with a range of doses and their egg viability assessed, and also tested to determine the impact of irradiation on male moth catch in the field. Female p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
(20 reference statements)
2
6
0
Order By: Relevance
“…This led to a seven‐fold reduction in the number of males attracted to females that had been irradiated at 300 Gy. This was similar to the effect reported with irradiated female T. anartoides (Suckling et al., ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This led to a seven‐fold reduction in the number of males attracted to females that had been irradiated at 300 Gy. This was similar to the effect reported with irradiated female T. anartoides (Suckling et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…Suckling et al. () found a significant difference in the attractiveness of irradiated and non‐irradiated female T. anartoides at higher doses, but this has not been previously investigated in E. postvittana .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, a recapture recorded on a particular day had occurred between that day and the more recent of the release days or the last day the trap was checked. Parameters affecting female moth performance have been examined elsewhere (Suckling et al., 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Despite attempts to model the effects of bi-sex or male-only releases of moths that suggested little benefit from females (Kean et al 2011), there is evidence for a background contribution of the female moths through communication disruption of males from calling virgin females, despite their irradiationreduced attractiveness and pheromone titre (Stringer et al 2013;Suckling et al 2006). Further, it has been suggested that there may be a benefit from sterile females acting as a ''sperm sink'' for wild males thereby reducing wild male fertility, which could contribute to part of the observed effect of population suppression.…”
Section: Operational Strategiesmentioning
confidence: 99%